A human chromosome 8 region with abnormalities in B cell, HTLV-I+ T cell and c-myc amplified tumours. - Mengle-Gaw, L (1987)
We describe a region of human chromosome 8q24 involved in variant Burkitt's lymphoma translocations, and where an interstitial deletion occurs in an HTLV-I+ ATL and three c-myc amplicons terminate. The deletion in the ATL DNA begins within 1.3 kb of the cloned Burkitt's lymphoma translocation breakpoint and ends within 700 bases of the cloned human equivalent of the rat retroviral insertion site, mis-1. In addition, three c-myc amplicons terminate in this region and the end of one of these (the colon carcinoma COL0320) maps within 12 kb of the distal end of the ATL deletion. This region is probably approximately 300 kb downstream of c-myc and the consistent occurrence of abnormalities in this region implies involvement in tumour aetiology in several different cell types.